2008
DOI: 10.1111/j.1399-5448.2008.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Young children (<5 yr) and adolescents (>12 yr) with type 1 diabetes mellitus have low rate of partial remission: diabetic ketoacidosis is an important risk factor

Abstract: Young children and adolescent children with T1DM had a low rate of partial remission. Metabolic control was poorest in young children, whereas higher dose insulin in adolescents because of insulin resistance contributes to less likelihood of having partial remission. DKA at diagnosis was associated with low rate of partial remission. It is possible that the low frequency of honeymoon phase in young children reflects more aggressive beta-cell destruction in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
90
6
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 17 publications
18
90
6
8
Order By: Relevance
“…The observed frequency of DKA in our population is in line with countries geographically near Denmark. A higher DKA rate was observed in the youngest age group (<5 years), which is consistent with previous studies undertaken in countries with a high incidence of type 1 diabetes [4,10,14,16,29]. The very young children (<2 years) had an undesirably high prevalence of DKA (48.3%), comparable with register studies from Sweden, Finland and Germany (39.5-54.9%) [15,30,31].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The observed frequency of DKA in our population is in line with countries geographically near Denmark. A higher DKA rate was observed in the youngest age group (<5 years), which is consistent with previous studies undertaken in countries with a high incidence of type 1 diabetes [4,10,14,16,29]. The very young children (<2 years) had an undesirably high prevalence of DKA (48.3%), comparable with register studies from Sweden, Finland and Germany (39.5-54.9%) [15,30,31].…”
Section: Discussionsupporting
confidence: 80%
“…In many patients, the clinical course of type 1 diabetes during the first year is characterised by residual endogenous insulin secretion (the remission phase) [16,22,23]. The heterogeneity of the remission phase and its duration are influenced by several factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlates with the results of other authors. Previous studies showed that children below the age of 5 had a low partial remission (Bowden et al 2008). Moreover, no remission was observed in children under the age of 3 (Abdul-Rasoul et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the first presentation of 10% to 70% of newly diagnosed children with DM1 is DKA (6). Also, these children encounter more problems than those newly diagnosed with DM1 including lower remission rate and poorer glycemic control (7,8).…”
Section: Introductionmentioning
confidence: 99%